1975
DOI: 10.1002/zaac.19754150302
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung von Chloro‐aqua‐Komplexen des Indium(III) und Röntgenstrukturanalyse von [InCl4(H2O)2][S4N3] – einem Tetrachloro‐cis‐diaqua‐Komplex des Indium(III)

Abstract: Die Verbindungen [InCl4(H2O)2][S4N3] (I) und In2Cl8H2O(S4N3)2 (II) wurden dargestellt und die Struktur der ersteren mittels Röntgenstrukturanalyse bestimmt. Die Verbindung kristallisiert in der Raumgruppe D 2h16 – Pnam mit den Gitterkonstanten a = 19,473 ű 0,003 Å, b = 6,183 ± 0,003 Å, c = 10,814 ± 0,003 Å. Die Verfeinerung nach der Methode der kleinsten Quadrate ergab einen R‐Wert von 4,9%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The In-C1 bonds can be viewed as single bonds and compare favourably with mean values of 2-383 A in InC13(PPh3) 2 (Veidis & Palenik, 1969), 2.448,& in (Et4N)2(InCIs) 2- (Brown, Einstein & Tuck, 1969), 2.45 A in [InC14(H20)2]- (Zeigler, Schlimper, Nuber, Weiss & Ertl, 1975) and 2.39 A in [MelnC12] (Hausen, Mertz, Veigel & Weidlein, 1974). Carty & Tuck (1975) propose a value of 2.30A for a single In-Cl bond length but this seems an underestimate.…”
mentioning
confidence: 82%
“…The In-C1 bonds can be viewed as single bonds and compare favourably with mean values of 2-383 A in InC13(PPh3) 2 (Veidis & Palenik, 1969), 2.448,& in (Et4N)2(InCIs) 2- (Brown, Einstein & Tuck, 1969), 2.45 A in [InC14(H20)2]- (Zeigler, Schlimper, Nuber, Weiss & Ertl, 1975) and 2.39 A in [MelnC12] (Hausen, Mertz, Veigel & Weidlein, 1974). Carty & Tuck (1975) propose a value of 2.30A for a single In-Cl bond length but this seems an underestimate.…”
mentioning
confidence: 82%
“…(dioxane)3 , by Whitlow & Gabe (1975). The existence of [InCl4(H20)2]-, originally postulated on the basis of solvent extraction (Tuck & Woodhouse, 1964a) and anion exchange (Dobud, Lee & Tuck, 1970) experiments, has been confirmed by the X-ray crystallographic work of Ziegler, Schlimper, Nuber, Weiss & Ertl (1975) who showed that the anion has the cis-stereochemistry proposed for lInC14(urea)2]-from vibrational spectra (Tuck & Woodhouse, 1964b). The early study of [InC15-(H20)] 2-, as the ammonium salt, by Klug, Kummer & Alexander (1948) gave In-Cl distances (2.58 ,~) which were substantially larger than those for any of the other compounds under discussion.…”
mentioning
confidence: 83%
“…Stephenson and Wilkinson's procedure yielded a microcrystalline product, Ru2(02CCH3)4C1, with acetate bridges. However, very recently Cotton et al 4 reported procedures for preparation of and crystal structures for five compounds of carboxylate-bridged RuII,ni dimers which included the Ru2(02CCH3)4(H20)2+ cation and the Ru2(02C-CH3)4C12™ anion. Also included was the hydrate, Ru2(02C-CH3)4C1-2H20.…”
Section: Introductionmentioning
confidence: 99%